Factors influencing when species are first named and estimating global species richness - WILSON, SIMON; HOULDING, BRETT (My University, 2015)
Estimates of global species richness should consider what factors influence the rate of species discovery at global scales. However, past studies only considered regional scales and/or samples representing <0.4% of all named species. Here, we analysed trends in the rate of description for all fish species (2% of all named species). We found that the number of species described has slowed for (a) brackish compared to marine and freshwater species, (b) large compared to small sized fish, (c) geographically widespread compared to localised, (d) species occurring in the tropics and northern hemisphere compared to southern hemisphere, and (e) neritic (coastal) species compared to pelagic (offshore) species. Most (68%) of the variation in year of description was related to geographic location and depth, and contrary to expectations, body size was a minor factor at just 6% (on a standardised scale). Thus most undiscovered species will have small geographic ranges, but will not necessarily be of smaller body size than currently known species. Accordingly, global assessments of how many species may exist on Earth need to account for geographic variation.
Keywords: Biodiversity; Biogeography; Marine; Freshwater; Fish; Taxonomy